ANALYSIS OF OZONE MASS TRANSFER IN A KENICS STATIC MIXER USING THE STEADY STATE BACK FLOW CELL MODEL (BFCM) - Mohamed. A. M. Saad; Dr.Abdullah. A. Elamari; Awad.E. Alshebani (مجلة البيان العلمية, 2023)
Static mixers have been successfully employed in water and wastewater treatment, particularly in water ozonation for disinfection and oxidation purposes. Producing higher concentration of ozone requires new contactors that operate efficiently at low gas/liquid ratio. The Kenics static mixer can meet these requirements and therefore enhance the ozone mass transfer rate [1]. The first objective of this study is to use the steady state back flow cell model (BFCM) developed by Tizaoui and Zhang [1] in order to predict the ozone concentration profile in the gas and the liquid phases along the Kenics static mixer. The second objective is to develop a Matlab code for the BFCM of the static mixer. The third objective of the steady state BFCM is to study the impact of the main characteristic parameters: back flow ratio of, the length of the Kenics static mixer, flow rate of water, and gas flow rate, volumetric liquid mass transfer coefficient and temperature on ozone concentration profile in the gas and liquid phases and respectively along the height of the Kenics static mixer.